SISI HUMANISME TERE LIYE DALAM NOVEL “REMBULAN TENGGELAM DI WAJAHMU” - Siti Musliah; Siti Nur Halimah; Ika Mustika (IKIP Siliwangi, 2018)
This article illustrates the humanism side of an author Tere Liye in the Rembulan sinking novel in Your Face which aims to provide motivation, message, and how to take the time. This study uses descriptive method, which aims to describe the results of research from samples in the form of quotations. Tere Liye reveals a variety of high humanity from responsibility, regret, despair, brotherhood, and compassion so that this novel contains moral values that we can learn and learn. The side of humanism in this article is motivated by the life story that occurs in the community. As human beings we must be able to respond to what happens in life not only see a single point of view, but must see the other side of the invisible. Tere Liye also reminds us that everything we do or do will turn to ourselves. The results of the analysis show that the figure of Tere Liye in the novel is a person who motivates us to live our lives, we must be realistic.